HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT KECEMASAN PADA LANSIA DALAM MENGHADAPI KEMATIAN - Rusdianah, Eva; Fika Diliyana, Yudha (Jurnal Biogenerasi, 2024)
Data released by the World Health Organization (WHO) in 2016 showed that 600 million people were elderly. Around 142 million people at that time lived in Southeast Asia. This research uses a cross-sectional approach. The research was conducted in Sayutan village, Parang District, Magetan Regency with a sample of 68 elderly people. The sampling technique uses simple random sampling with the Spearman Rank test. The support variable shows 35 with a percentage (51.5%) getting good family support and there are 19 respondents with a percentage (27.8%) with a sufficient percentage and there are 14 respondents with a percentage (20.6%) with a poor percentage, while the 10 respondents had a level of anxiety with a percentage (14.7%). The results of the Spearman rank statistical test analysis obtained a value of p = 0.010 and r = 0.267. because the p value (0.010) < α = 0.05 means that HO is rejected and HI is accepted, meaning that there is a relationship between family support and the level of anxiety of the elderly in facing death in Sayutan Village, Parang District, Magetan Regency.